Electronic, structural and optical properties of zincblend and wurtizite cadmium selenide (CdSe) using density functional theory and hubbard correction - Edossa, Teshome Gerbaba; Woldemariam, Menberu (Physics and Chemistry of Solid State, 2021)
Zinc blend (zb) and wurtizite (wz) structure of cadmium selenide (CdSe) is determined using density-functional theory within local density approximation (LDA), generalized gradient approximation (GGA), Hubbard-correction (GGA+U) and Hybrid functional approximation (PBE0 or HSE06). The first principle pseudopotential plane wave is used and the relaxed atomic position for the CdSe in zb and wz structure was obtained by using total energy and force minimization method following the Hellmann Feynman approach. The convergence test of total energy with respect to cutoff energy and k-point sampling is performed . The equilibrium lattice constant and unit cell volume of CdSe in both phases are calculated and the obtained value is compared` with experimental values. In addition the band gap of CdSe is analyzed using DFT within LDA, GGA, DFT+U and PBE0 to approximate the unknown exchange correlation functional. The band gap values obtained using LDA and GGA are severally under estimated due to their poor approximation of exchange-correlation potential. This problem was improved by using projector augmented-wave pseudopotential within Hubbard-correction (GGA+U) and the hybrid functional approximation. Optical properties: complex and real parts of dielectric function, energy loss spectrum and absorption coefficient of CdSe in both ZB and WZ phase were studied.